Metric Characteristics of the Tests for Dynamic Balance Evaluation - Sarabon, N.; Zacirkovnik, T.; Rosker, J.; Loefler, S. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2013)
Different dynamic balance tests help to identify specific balance deficits in elderly and various population groups. In addition, dynamic balance tests have proved useful in identifying potential locomotor-system injury risk factors. These tests differ in the quality of their metric characteristics which could influence their applicability to measure balance in different clinical groups. Reliability, validity, sensitivity and objectivity define metric characteristics of an individual test. This paper provides an overview of the available scientific literature regarding measurement characteristics of the most commonly used dynamic balance tests. Reliability (intra-session, inter-session, inter-tester and intra-tester), sensitivity, validity and ability to predict possible balance impairing trauma and disease are presented. Clinical balance tests (balance assessed by analogue scales), functional reach, star excursion tests and out step tests were most frequently studied for their metric characteristics. In general intra-session reliability proved to be slightly higher than inter-session reliability. On the contrary there is a lack of reports on inter-tester and intra-tester reliability, especially for star excursion tests and for the tests performed on an unstable surface. Tests differ in the validity; possibly resulting from use of different reference standards. In addition factors such as age, fatigue, learning, and anthropometric characteristics have been shown to affect dynamic balance. Majority of tests were successfully implemented in the process of identifying fall prone individuals. However the reports on potential of dynamic balance tests to help predict other lower extremity injury or sports performance are sparse. In general dynamic balance measuring tests (not all parameters) proved to have sufficient metric characteristics for their practical application. However individual parameters and goals of balance assessment should be considered, when choosing the most appropriate test.
Keywords: dynamic balance; metric characteristics; testing; reliability; validity; sensitivity